DEVELOPMENT OF INTEGRATED SERVICE APPROACH ON DEPARTEMENT OF SOCIAL STUDIES EDUCATION - Holilah, Mina - (International Journal Pedagogy of Social Studies, 2019)
The objective condition of the institution regarding the need for department Â professional services to students based on established quality standards. Higher education is not only seen as a center of knowledge, a center of research, and a center of community service, but also an institution that needs to compete to guarantee services to users in this case are students. The tight competition of tertiary quality and the demands of the community for quality that is oriented to the value of service users (customer value) ultimately pressures the organization to be able to respond quickly (responsiveness) including prioritizing student satisfaction which is currently used as a benchmark for excellence in higher education competitiveness . The education services of the Social Studies Study Program in this study are focused on the performance of the Head of Study Program, the performance of teaching lecturers, and the performance of administrative staff services. In connection with its function which is always related to students, the Study Program service is expected to realize quality education. However, this ideal condition is inseparable from the factual conditions in the field which shows that there are still some shortcomings of services that are complained of by students and requires further research.